A commoning framework for environmental archaeology: beyond resource management in Indigenous North America - Jenkins, Jessica A.; Gallivan, Martin D.; Hatch, Brad (Frontiers in Environmental Archaeology, 2026)
Environmental archaeology has often relied on common-pool resource models to interpret past human-environment relationships, yet these frameworks overlook Indigenous ontologies grounded in kinship with land, water, and more-than human beings. We propose commoning as a complementary approach that centers reciprocity, relational care, and cultural meaning alongside institutional regulation. Drawing on archaeological evidence from Virginia's Chesapeake Bay, we show how commoning reveals Indigenous environmental governance as a world-making practice. This framework advances environmental archaeology by integrating Indigenous epistemologies, supporting collaborative methods, and linking archaeological interpretation to contemporary environmental justice.